Penegakan Hukum Terhadap Ujaran Kebencian Berbasis Suku di Media Sosial: Studi Empiris Di Kecematan Donggo - Alias Rangga; Iksan Iksan; Yuddin Chandra Nan Arif (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the enforcement of laws against ethnic-based hate speech occurring on social media in Donggo Subdistrict, Bima Regency. The main focus of this study is on how the law enforcement process is carried out and the various obstacles faced by authorities in addressing hateful content that attacks the identity of the “Dou Donggo” community. This study employs an empirical legal method using a sociological-juridical approach and qualitative analysis. Data were collected through in-depth interviews with law enforcement officials, local government representatives, community leaders, and social media users, supplemented by observations and documentation. The research findings indicate that the handling of ethnic-based hate speech is carried out through two mechanisms: the formal legal channel, which refers to the provisions of the ITE Law and Constitutional Court rulings; and the social channel, through amicable resolution involving traditional leaders. However, the effectiveness of law enforcement remains hampered by weak electronic evidence, low public legal awareness, and the strong preference for amicable settlements, which have the potential to sideline formal legal processes. Therefore, there is a need to improve digital literacy, strengthen cyber forensic capabilities, and harmonize customary mechanisms with criminal law.